Analisis Aisas (Attention, Interest, Search, Action, Share) pada Pengunjung the Lodge Maribaya Lembang - Gina Amalia; Fahrurozy Darmawan; Yuwana M. Marjuka (Fakultas Pariwisata Universitas Pancasila, 2017)
The attractions in West Bandung district these days are in great demand by the tourists, one of them being The Lodge Maribaya. The Lodge Maribaya is located in Cibodas Village, Lembang sub-district. The popularity of The Lodge Maribaya is also thanks to the implementation of effective and efficient marketing communications. One of them is through internet marketing communication. This tourists’ convenience in searching tour destination is the one that creates the AISAS (attention, interest, search, action, share) model. The purpose of this research is to analyze the application of AISAS model according to Sugiyama (2011) towards The Lodge Maribaya Lembang’s visitors. The method used is qualitative research with there search focus being the application of the visitors’ AISAS using the data reduction, data display and conclusion This research needs 100 respondent samples which are the visitors of The Lodge Maribaya. According to the result of data processing, it is known that the attention, interest, search, action and share stage as a whole gets 90,5% percentage. With that being said, this research shows that most of The Lodge Maribaya’s visitors has applied the AISAS model in their visiting behavior